Owner-managers’ transformational leadership behaviours and human resource strategies: A case of small fast-food restaurants in South Africa - Lebohang Ntlhanngoe (SA Journal of Human Resource Management, 2021)
Orientation: The proliferation of fast-food restaurants in South Africa calls for transformational leadership (TL) to keep the businesses afloat, through the application of competitive strategic human resource (HR) practices. However, there is shortage of evidence on how TL behaviours of owner-managers in this sector are related to their choice of HR strategies.